Developing a New Parameterization Scheme of Temperature Lapse Rate for the Hydrological Simulation in a Glacierized Basin Based on Remote Sensing - Wanying Song; Handuo Tang; Xueyan Sun; Yuxuan Xiang; Xiaofei Ma; Hongbo Zhang (Remote Sensing, 2022)
Temperature lapse rate (TLR) is an important parameter for simulations of snow/glacier melts in alpine watersheds. However, the traditional scheme estimates TLR mainly based on a limited number of stations and may not be suitable for alpine watersheds with scarce observations. To overcome this problem, this study developed a new basin-oriented TLR scheme based on Moderate Resolution Imaging Spectroradiometer (MODIS) land surface temperature data which was applied in a typical glacierized watershed on the northern slope of the Himalayas. The new TLR scheme was evaluated by comparison with the station-based traditional TLR scheme in terms of performance in simulations of both snow cover area and runoff using the same hydrological model. The results showed that the monthly TLRs estimated by the new scheme presented a more reasonable seasonal pattern than those estimated by the traditional scheme. The model using the new TLR scheme showed better performance in discharge simulations of low-runoff months than that using the traditional TLR scheme. The R-squared value of multiyear mean monthly snow cover area of the former (0.82) was also higher than that of the latter (0.56). This study provides an efficient framework for estimating TLR based on remote sensing for alpine watersheds with scarce observations.